Outcome of capacity building in mental health for well-being volunteers - Yaresheemi, Shivanand; Elangovan, Aravind Raj; Jangam, Kavita; Doraiswamy, Padmavathy; Sharma, Manoj Kumar; Chandra, Prabha S. (Frontiers in Psychiatry, 2023)
Volunteering is any activity in which time is given to assist another individual, group, or organization.. It assists people who want to get involved in philanthropic programs that help volunteers develop awareness and lead healthier personal and social lives. Several volunteers have received specialized training in the fields in which they volunteer, such as health, mental health, education, or emergency rescue. Volunteers are rendering intervention in different areas in mental health. They are providing psychosocial support to the individuals, groups, community, promoting mental health through conducting various mental health awareness programs in the community. There is a growing concern about mental health in India due to the inaccessibility of services. The National Institute of Mental Health and Neuro Sciences (NIMHANS) being a premier institute for mental health, is devising innovative approaches to mental health care to reach the unreachable. One such initiative was to build the capacity of volunteers in the community who are interested in working for the cause of mental health.The objective of this study was to evaluate the outcome of the well-being volunteer program.